Pengembangan Game Edukasi Kebersihan Lingkungan Pesisir Pantai Menggunakan Algoritma Fisher-Yates Shuffle - Khanaya Adjie Akbar; Iedam Fardian Anshori (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The increasing volume of waste in coastal areas, particularly in the Anambas region, poses a serious threat to marine ecosystems and public health. This study aims to develop an educational game themed on coastal cleanliness for elementary school students, utilizing the Fisher-Yates Shuffle algorithm and the Game Development Life Cycle (GDLC) method. The research employs a descriptive-qualitative approach with software engineering, involving 20 participants (5 teachers and 15 students) from SDN 001 Payalaman as the sample. Data were collected through observation, interviews, and Likert-scale questionnaires, and analyzed using qualitative-descriptive techniques with triangulation. The results show that the game is well-received, increases student engagement, and enhances understanding of environmental issues. The findings indicate that the game effectively delivers interactive educational content and motivates students to care for the coastal environment. In conclusion, the game is suitable as a thematic learning medium in coastal schools, though future research should expand the sample and explore additional features for broader impact.